2010
DOI: 10.1111/j.1752-7325.2009.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and dental caries in a group of preschool children in Mexico

Abstract: Obesity appears to be associated with dental caries in the primary dentition of preschool Mexican children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 21 publications
2
72
1
13
Order By: Relevance
“…We are not the first to study the relationship between S-ECC and BMI [14, 16, 19, 23, 24, 27, 28]. The significant association between S-ECC and higher BMI z-scores or overweight/obesity highlighted in this research is in agreement with other studies [13, 27, 35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We are not the first to study the relationship between S-ECC and BMI [14, 16, 19, 23, 24, 27, 28]. The significant association between S-ECC and higher BMI z-scores or overweight/obesity highlighted in this research is in agreement with other studies [13, 27, 35].…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, other large population-based studies have not found any significant association between BMI and caries experience after controlling for confounders [23, 24, 29, 37]. However, many studies in the area of BMI and caries report mean BMI, BMI percentiles, or mean weight on populations of varying ages and of mixed gender [14, 16, 28, 37–40]. The use of z-scores adjusts for both age and gender and thus allows for more meaningful reporting of means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 A cohort study conducted in Mexico among 4-5 yrs old children in Mexico showed that overweight and at-risk overweight children had higher caries prevalence than children who were not overweight and caries was also associated with sugar consumption, bottle feeding, smoking at home and tooth brushing ≤ once per day. 25 Another study conducted in Manitoba showed that significantly more children with S-ECC had significantly higher mean BMI z-scores than caries-free children (0.78 ± 1.26 vs. 0.22 ± 1.36, p = 0.002). 34 Also, there were many studies with no statistically significant association between dental caries and different categories of BMI i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Studies in countries such as Sweden [11], Germany [12], Brazil [13], Mexico [14], India [15], and Thailand [16] all showed significant association between overweight/obesity with caries among obese children. On the other hand, studies from USA [17,18], France [19], Brazil [20], and Iran [21], did not find any significant association between obesity and caries experience among the children.…”
mentioning
confidence: 99%